1993
DOI: 10.1080/09515079308254115
|View full text |Cite
|
Sign up to set email alerts
|

Graduate psychology students' perceptions of the scientist-practitioner model of training

Abstract: Since its inception over forty years ago, there has been considerable controversy regarding the viability of the scientist-practitioner model for training professional psychologists. The present study utilized a combination of qualitative and quantitative research methods to assess graduate psychology students ' (n = 24) perceptions of this training model. Counselling, clinical, and school psychology students participated in semi-structured interviews and were administered the Vocational Preference Inventory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…To help students with this decision-making process, Leong and Zachar (1991) developed a scale called the Scientist-Practitioner Inventory (SPI). A series of studies over the past 15 years has found that interests in both scientist and practitioner activities are internally consistent and that scientist and practitioner interests are negatively correlated for graduate students and psychologists, but positively correlated for undergraduates (Aspenson et al, 1993;Leong & Zachar, 1991;Manning, Zachar, Ray, & LoBello, 2006;Zachar & Leong, 2000). Zachar and Leong (2000) showed that these specialty interests predict the actual work behaviors of psychologists and the probable future behaviors of graduate students.…”
Section: Career Specialty Choice In Psychologymentioning
confidence: 99%
“…To help students with this decision-making process, Leong and Zachar (1991) developed a scale called the Scientist-Practitioner Inventory (SPI). A series of studies over the past 15 years has found that interests in both scientist and practitioner activities are internally consistent and that scientist and practitioner interests are negatively correlated for graduate students and psychologists, but positively correlated for undergraduates (Aspenson et al, 1993;Leong & Zachar, 1991;Manning, Zachar, Ray, & LoBello, 2006;Zachar & Leong, 2000). Zachar and Leong (2000) showed that these specialty interests predict the actual work behaviors of psychologists and the probable future behaviors of graduate students.…”
Section: Career Specialty Choice In Psychologymentioning
confidence: 99%
“…After analyzing the qualitative and quantitative data separately, the results were used to help answer the three research questions. Aspenson et al (1993), Baker and Siryk (1986), Blustein, Phillips, Jobin-Davis, Finkelberg, and Rourke (1997), Gaston and Marmar (1989), and Guernina (1998) are other examples of studies that used concurrent nested designs.…”
Section: Illustration Of Mixed Methods Research Designs and Key Desigmentioning
confidence: 99%
“…During 1949 it was recommended that training programmes be structured according to a scientist-practitioner model, in which research and application of theory would be equally important (Aspenson & Gersh, 1993;Benishek, 1998;Stoltenberg, Pace, Kashubeck-West, Biever, Patterson & Welsch, 2000). The professional-practitioner model was suggested as an alternative training model to the scientist-practitioner model.…”
Section: Training Contexts and The Development Of Professional Identitymentioning
confidence: 99%